O impacto dos ciclos econômicos nos accruals discricionários das empresas - Webber, Fabiano Lima (Universidade do Vale do Rio dos Sinos, 2021)
Firms are influenced by the environment in which they operate, a fact that can interfere on manager’s decision to manage their earnings. In light of this, the present research analyzed the impact of economic cycles on the discretionary accruals of companies in 5 latin-american countries whose data were collected from the quarterly financial statements from 1996 to 2017, using the Economática software. The data representing economic cycles (interest rate, exchange rate and GDP) were collected quarterly from each of the countries surveyed. Discretionary accruals were calculated based on the Jones (1991) and Modified Jones (DECHOW, SLOAN, SWEENEY, 1995) models. Through an elaborated econometric model, it was verified if there is an influence of the interest rate variation, exchange rate variation and GDP variation in the discretionary accruals of both models. The base models were tested without and with control variables presented by results management studies. The results of the research indicated that the variation of the GDP does not influence the discretionary accruals in any of the proposed models. The interest rate variation has a statistically significant relationship with the dependent variable in 2 of the 36 models tested. The exchange rate variation, on the other hand, is statistically relevant to the discretionary accruals in 15 of the 36 calculated models.
Keywords: Gerenciamento de resultados; Accruals discricionários; Ciclos econômicos; Taxa de juros; Taxa de câmbio; Produto interno bruto; Earnings management; Discretionary accruals; Economic cycles; Interest rate; Exchange rate; Gross domestic product; GDP; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis